Smart Greenhouse Design for Strawberry Cultivation in Pandanrejo, Batu City - Bustomi, Muhammad Arief; Indarto, Bachtera; Fatimah, Iim; Suyatno, S; Sudarsono, S; Pramono, Yono Hadi (Institut Teknologi Sepuluh Nopember, 2023)
Batu City, which is famous as a tourist city, is not only an urban area. Most of the Batu city area is a rural area, especially the northern area which is included in the Bumiaji sub-district. As a tourist area, Batu City has a large enough economic potential to improve the welfare of its people. Most of the people of Batu city who live in rural areas are fruit and vegetable farmers. Pandanrejo village in Bumiaji sub-district is an example of a strawberry-producing village in Batu city. Various problems are faced by strawberry farmers in Pandanrejo village. One of them is related to the uncertain weather conditions in their village. The ITS Physics department team provides solutions related to these weather conditions with an innovative climate conditioning technology that can be applied in agriculture. This technology is a smart greenhouse in which there is control of environmental conditions for strawberry plants. With the application of smart greenhouse technology, it is expected to increase the productivity of strawberries and the welfare of the farming community of Pandanrejo village, Batu city.